2022
DOI: 10.1002/acr.24760
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patient‐Reported Outcomes Measurement Information System Computerized Adaptive Testing Versus Fixed Short Forms in Juvenile Myositis

Abstract: Objective Patient‐Reported Outcomes Measurement Information System (PROMIS) measures can be administered via computerized adaptive testing (CAT) or fixed short forms (FSFs), but the empirical benefits of CAT versus FSFs are unknown in juvenile myositis (JM). The present study was undertaken to assess whether PROMIS CAT is feasible, precise, correlated with FSFs, and less prone to respondent burden and floor/ceiling effects than FSFs in JM. Methods Patients 8–17 years of age (self‐report and parent proxy) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The CAT and SF instruments have been previously evaluated in the PROMIS Pediatric measures, but in a different cohort of 67 pediatric patients with juvenile myositis. 29 The present study confirms many of this study's findings and offers additional key insights. As in our study, Patel et al found that the CAT and SF had similar scores and correlated highly, and that the CAT had fewer floor effects than the SF.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The CAT and SF instruments have been previously evaluated in the PROMIS Pediatric measures, but in a different cohort of 67 pediatric patients with juvenile myositis. 29 The present study confirms many of this study's findings and offers additional key insights. As in our study, Patel et al found that the CAT and SF had similar scores and correlated highly, and that the CAT had fewer floor effects than the SF.…”
Section: Discussionsupporting
confidence: 88%
“…Patel et al recommended a follow-up study such as ours to better optimize stopping rules. 29 We showed that CAT offers improvement in floor effects and precision over the SF even with a stopping rule at six questions, which carries the added benefit of minimizing respondent burden.…”
Section: Discussionmentioning
confidence: 74%
“…68,69 The fixed short form had the strongest evidence of the four versions with 'very low' quality internal consistency, 77 'low' quality reliability, 71,74,77,86,87 and 'low' quality construct validity. 71,73,77,86,87…”
Section: Promis Pppismentioning
confidence: 99%
“…Physician Global Damage VAS and Myositis Damage Index scores were obtained at baseline and week 24 (11). Health-related quality of life was parent-assessed at each visit using the Child Health Questionnaire 50-item parent form (CHQ-PF50), the Dermatology Life Quality Index (DLQI), and the Patient-Reported Outcomes Measurement Information System (PROMIS) fatigue scale (18,19). Safety analysis.…”
Section: Methodsmentioning
confidence: 99%